Dielectric and infrared spectroscopy characterization of Co–Al layered double hydroxides - Zamaraite, Ilona (2021)
Layered double hydroxides (LDHs) are natural 2D materials with promising functionalities. A comprehensive understanding of physical properties (such as electrical or optical) is critical for their current and future applications. Herein, dielectric and infrared spectroscopy to extensively characterize thermal behavior of dynamic effects in cobalt–aluminum LDH with Co-to-Al ratio of 2 and intercalated with nitrate is applied. The dielectric response of the vacuum-dried LDH shows noticeable relaxation processes in the radio frequency range. A detailed analysis of the relaxations allows assigning them to the dynamics of water clusters confined in the interlayer. Infrared spectroscopy enables the characterization of bands attributed to the O─H stretching of these water clusters. It is found that a decrease in temperature results in freezing of the water clusters in the interlayers and in the coexistence of water-like and ice-like clusters network in this LDH.